2012
DOI: 10.1021/np300069z
|View full text |Cite
|
Sign up to set email alerts
|

The Cephalostatins. 22. Synthesis of Bis-steroidal Pyrazine Pyrones

Abstract: Cephalostatin 1 (1), a remarkably strong cancer cell growth inhibitory trisdecacyclic, bis-steroidal pyrazine isolated from the marine tube worm Cephalodiscus gilchristi, continues to be an important target for practical total syntheses and a model for the discovery of less complex structural modifications with promising antineoplastic activity. In the present study, the cephalostatin E and F rings were greatly simplified by replacement at C-17 with an α-pyrone (in 12), typical of the steroidal bufodienolides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…It has been suggested that the cytotoxic potential of these natural steroid dimers is probably mediated by their ability to target oxysterol bending protein involved in signal transduction [45]. Several cephalostatin analogues including some of them containing sugar moieties (2-10 and 29-34), were synthesized and their cytotoxic potential was evaluated [5,8]. Among them, diol pyrazine dimer 4, diol rhamnoside pyrazine dimer 7 and polyhydroxy rhamnoside pyrazine dimer 10 were found to inhibit the growth of cancer cells of the murine P388 lymphocytic leukemia cell line as well as against a range of human cancer cell lines, whereas steroid dimers, diacetate pyrazine dimer 30 and dione pyrazine dimer 31 were active against the murine 388 cell line.…”
Section: Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the cytotoxic potential of these natural steroid dimers is probably mediated by their ability to target oxysterol bending protein involved in signal transduction [45]. Several cephalostatin analogues including some of them containing sugar moieties (2-10 and 29-34), were synthesized and their cytotoxic potential was evaluated [5,8]. Among them, diol pyrazine dimer 4, diol rhamnoside pyrazine dimer 7 and polyhydroxy rhamnoside pyrazine dimer 10 were found to inhibit the growth of cancer cells of the murine P388 lymphocytic leukemia cell line as well as against a range of human cancer cell lines, whereas steroid dimers, diacetate pyrazine dimer 30 and dione pyrazine dimer 31 were active against the murine 388 cell line.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…These studies provided further evidence on the essential structure-activity-relationships (SAR) features required for cephalostatins' cytotoxic properties including the need for a C-14 double bond, C-12 oxygenation (alcohol or ketone), and a 17α-hydroxy group for optimum activity. It was suggested that there might be several other less obvious molecular features of the cephalostatintype steroids that are critical to their significant potency against cancer cell growth and mechanisms of biological activity [8].…”
Section: Cytotoxicitymentioning
confidence: 99%
“…In addition, pyrazine heterocycles have also been finding applications in materials science 8. Some naturally occurring pyrazine derivatives – tetramethylpyrazine,9 a representative barrenazine,10 and cephalostatin1a – are shown in Figure 1. The majority of the natural pyrazines are derived from amino acids 11.…”
Section: Introductionmentioning
confidence: 99%
“…After 15 years of challenging research directed at isolation and structural elucidation of the anticancer-active constituents of the marine worm Cephalodiscus gilchristi , we reported the discovery of cephalostatin 1 ( 1 ) in 1988 in 8.4 × 10 –4 % yield . Cephalostatin 1 consists of two highly oxygenated hexacyclic steroid monomers linked by a pyrazine core .…”
mentioning
confidence: 99%
“…More recently, an enantioselective route was reported by Shair and colleagues . A number of research groups have undertaken the synthesis of cephalostatin analogues in an effort to provide synthetically accessible biosteroidal derivatives with promising cancer cell growth inhibition. One of these modifications, hybrid 25- epi -ritterostatin G N 1 N ( 2 ), has proved to be the most promising owing to its subnanomolar activity (GI 50 0.48 nM) against the NCI-60 cell line . Not only was 2 more cytotoxic than the natural isomer (ritterostatin G N 1 N ; GI 50 14 nM), but its convergent synthesis yielded a more accessible structure.…”
mentioning
confidence: 99%